2014
DOI: 10.1021/am5049338
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Biological Functions of Osteoblasts and Bone Formation by Zn-Incorporated Coating on Microrough Titanium

Abstract: To improve the biological performance of titanium implant, a series of Zn-incorporated coatings were fabricated on the microrough titanium (Micro-Ti) via sol-gel method by spin-coating technique. The successful fabrication of the coating was verified by combined techniques of scanning electron microscopy, surface profiler, X-ray diffraction, X-ray photoelectron spectroscopy, and water contact angle measurements. The incorporated zinc existed as ZnO, which released Zn ions in a sustained manner. The Zn-incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 63 publications
4
95
0
Order By: Relevance
“…More importantly, in vivo evaluations verified that the treatment could efficiently promote new bone formation in early times . Shen et al found that the micro‐structure contributed to the expression levels of type I collagen (COLIA 1), osteopontin (OPN), and osteocalcin (OCN) genes of MG63 cells …”
Section: Introductionmentioning
confidence: 99%
“…More importantly, in vivo evaluations verified that the treatment could efficiently promote new bone formation in early times . Shen et al found that the micro‐structure contributed to the expression levels of type I collagen (COLIA 1), osteopontin (OPN), and osteocalcin (OCN) genes of MG63 cells …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the surface characteristics of implants play a critical role in determining the cell and tissue responses. 1,2 Surface characteristics such as surface topography, wettability, roughness, and composition have been reported to markedly modulate protein adsorption and cell proliferation and differentiation in vitro and influence bone-to-implant contact as well as bone regeneration in vivo. 3,4 Hence, to achieve a desirable integration ability of titanium implants with bones, various surface modifications have been adopted to enable the substrates with specific properties to improve the bioactivity, including plasma immersion ion implantation, 5 deposition of calcium phosphate coatings, 6 and immobilization of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…4A & C) and free bacteria in medium (Fig. 4B & D) after culture for 4 h, 24 h and 72 h [44,45], respectively. For the adhered S. epidermidis (Fig.…”
Section: Bacterial Viabilitymentioning
confidence: 97%